Community aspirations and collective action - Christina Martini; Marcela Ibanez; Menusch Khadjavi (Georg-August-Universität Göttingen, Research Training Group (RTG) 1666 - GlobalFood, 2021)
We propose that community aspirations defined as the preferences for goals that increase communal well-being are an important determinant of cooperation in collective action problems. This paper conceptualizes community aspirations and investigates whether the proposed measure is associated with cooperation. The second part of the paper presents the results of a randomized controlled trial that aimed at lifting community aspirations by presenting real-world examples of successful collective action. Survey and experimental data from rural Zambia indicate that compared with current situation, individuals hold optimistic community aspirations. We find some supporting evidence for a positive correlation between community aspirations and cooperation measured using experimental and survey data. Exposure to the examples of cooperation increases cooperation, but has a negative effect on community aspirations. Instead, we find that the mechanism could be through a change in the perceived norm of cooperation.
Keywords: C93; D70; D91; O12; 330; aspiration; cooperation; role model; public good; social norms; development